Electrochemical Behavior and Determination of Rutin on Modified Carbon Paste Electrodes - Pavla Macikova; Vladimir Halouzka; Jan Hrbac; Petr Bartak; Jana Skopalova (The Scientific World Journal)
The performances of ionic liquid (1-hexyl-3-methylimidazolium-bis(trifluoromethylsulfonyl)imide, IL/CPE) and iron phthalocyanine (IP/CPE) modified carbon paste electrodes in electroanalytical determinations of rutin were evaluated and compared to the performance of unmodified carbon paste electrode (CPE). Cyclic voltammetry (CV), differential pulse voltammetry (DPV), differential pulse adsorptive stripping voltammetry (DPAdSV), and amperometry were used for rutin analysis. The best current responses of rutin were obtained at pH 4.0 for all tested techniques. IL/CPE electrode was found to perform best with DPAdSV technique, where a detection limit (LOD) as low as 5 nmol L-1 of rutin was found. On the other hand, IP/CPE showed itself to be an optimum choice for DPV technique, where LOD of 80 nmol L-1 was obtained. Analytical applicability of newly prepared electrodes was demonstrated on determination of rutin in the model samples and the extracts of buckwheat seeds. To find an optimum method for buckwheat seeds extraction, a boiling water extraction (BWE), Soxhlet extraction (SE), pressurized solvent extraction (PSE), and supercritical fluid extraction (SFE) were tested.